STRUKTUR MATA PENCAHARIAN PENDUDUK DAN DIVERSIFIKASI PERDESAAN DI KECAMATAN TENGARAN KABUPATEN SEMARANG - Hardati, Puji; Rijanta, R.; Ritohardoyo, Su (Jurnal Geografi, 2014)
This paper aims to determine the livelihoods structures and rural diversificationin Tengaran Sub District of Semarang Regency. Using secondary data, tables andmaps analysis are expected to provide an overview of the purpose. The results ofthe study showed that the structure of livelihood in study area was various. Theagricultural sector still become favorite in rural activities. There had beenchanges to industry and services sector, even though very small. The dominantservices sector are industrial workers, buildings, and transportation. Ruraldiversification has taken place, with a diversification index of 4.4. In spatialframe, diversification index is not similiar or very various. The villages withvarying structures livelihoods have higher diversification index.